Scabies as a Health Challenge in Coastal Areas and Its Control strategie, Indonesia : A Review - Yulya Lasmita; Magvirah Tuljannah (Journal of Epidemiology and Health Science, 2025)
Background: Scabies is a contagious skin disease caused by the infestation of Sarcoptes scabiei mites. Although it is a global health concern, scabies remains particularly prevalent in areas with poor water sanitation, inadequate personal hygiene, and limited access to healthcare services. Coastal communities and high-density settlements are especially vulnerable due to environmental, economic, and social factors that exacerbate the spread of skin-related infectious diseases. Objective: This study aims to identify and analyze the factors associated with the incidence of scabies, particularly in coastal areas and densely populated communities, with a focus on preventive and control strategies applicable in the Kolaka region. Methods: A systematic literature review was conducted by examining scientific articles related to scabies prevalence in coastal and high-density populations. The databases used for the literature search included PubMed and Google Scholar. Articles were selected based on inclusion criteria focusing on scabies, sanitation, and public health interventions, with publication years ranging from 2015 to 2025. Results: The findings indicate that poor personal hygiene, inadequate sanitation, and overcrowded living conditions are key risk factors for scabies transmission. Community health education, improvements in water and sanitation facilities, and medical interventions such as mass drug administration using ivermectin or permethrin have proven to be effective control strategies. Conclusion: Integrated, community-based interventions that combine education, sanitation improvement, and medical treatment are essential for reducing the incidence of scabies in coastal and densely populated areas. Keywords: Scabies, Coastal Areas, Sanitation, Health Education, Control Strategies, Indonesia.